2003
DOI: 10.1097/00004872-200312000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Systolic blood pressure variability as a risk factor for stroke and cardiovascular mortality in the elderly hypertensive population

Abstract: , on behalf of the Syst-Eur investigatorsObjective To investigate whether baseline systolic blood pressure variability was a risk factor for stroke, cardiovascular mortality or cardiac events during the SystEur trial.Design The Syst-Eur study was a randomized, doubleblind, placebo-controlled trial, powered to detect differences in stroke rate between participants on active antihypertensive treatment and placebo. Systolic blood pressure variability measurements were made on 744 participants at the start of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
237
5
10

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 321 publications
(259 citation statements)
references
References 27 publications
(27 reference statements)
7
237
5
10
Order By: Relevance
“…6 Most studies have found that high 24-hour BP variability is associated with organ damage and may contribute to cardiovascular risk prediction, over and beyond mean BP. [7][8][9][10][11][12][13][14][15][16][17] However, the degree to which variability improves the prediction of cardiovascular risk is controversial. [18][19][20] Previous studies have shown that nighttime BP is generally a better predictor of cardiovascular outcomes than daytime BP in patients with hypertension, and diminished nocturnal decline in BP is associated with or predictive of organ damage and cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%
“…6 Most studies have found that high 24-hour BP variability is associated with organ damage and may contribute to cardiovascular risk prediction, over and beyond mean BP. [7][8][9][10][11][12][13][14][15][16][17] However, the degree to which variability improves the prediction of cardiovascular risk is controversial. [18][19][20] Previous studies have shown that nighttime BP is generally a better predictor of cardiovascular outcomes than daytime BP in patients with hypertension, and diminished nocturnal decline in BP is associated with or predictive of organ damage and cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Further, large BP variability is an independent risk factor for cardiovascular events in hypertensive patients. [10][11][12] However, the mechanism by which hypertensive cardiac remodeling is aggravated by increased BP variability remains unknown. Recently, we have created a rat model exhibiting a combination of hypertension and large BP variability by performing bilateral sinoaortic denervation (SAD) in spontaneously hypertensive rats (SHRs).…”
Section: Introductionmentioning
confidence: 99%
“…2 Furthermore, elevated systolic blood pressure (SBP) is associated with greater risk than elevated diastolic blood pressure (DBP) in older persons. 2,[7][8][9] In the last decade, a number of clinical trials have consistently shown that successful antihypertensive therapy significantly decreased rates of cerebrovascular and cardiovascular morbidity and mortality in the elderly. 3,4,[9][10][11] Hypertension is the most common primary diagnosis from 35 million doctor visits in the United States.…”
Section: Introductionmentioning
confidence: 99%